A BNNS@SiO2@Al2O3 / cashew phenol-based flame-retardant and thermally conductive epoxy composite material and its preparation method

CN120682595BActive Publication Date: 2026-10-09JIANGNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510709793.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-29
Publication Date
2026-10-09
Estimated Expiration
2045-05-29

AI Technical Summary

Technical Problem

但是混合填料之间的粘合力只取决于物理沉积和吸附,这不可避免地会导致更多的缺陷和界面热阻,恶化声子散射,产生填料团聚

Benefits of technology

[0027] 1. The epoxy resin composite material prepared by this invention has higher thermal conductivity: Compared with the traditional method of introducing single or mixed fillers to improve the thermal conductivity of epoxy resin composite materials, this material constructs a ternary thermally conductive system BNNS@SiO2@Al2O3. Through the ternary heterostructure thermally conductive filler, the characteristics of multi-element fillers can be fully utilized, forming a more efficient thermal conduction path in the matrix, and effectively avoiding interfacial thermal resistance and incomplete dispersion of fillers, ultimately achieving a synergistic improvement effect on the thermal conductivity of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005426780940000051
    Figure BDA0005426780940000051
  • Figure BDA0005426780940000061
    Figure BDA0005426780940000061
  • Figure BDA0005426780940000071
    Figure BDA0005426780940000071
Patent Text Reader

Abstract

The application discloses a BNNS@SiO2@Al2O3 / cashew phenol-based flame-retardant heat-conducting epoxy composite material and a preparation method thereof. Through condensation reaction between cashew phenol and phosphorus-containing compounds, a phosphorus-containing cashew phenol-based flame-retardant epoxy monomer and a flame-retardant curing agent are successfully prepared, so that the composite material has more excellent flame-retardant performance. Meanwhile, the ordered arrangement BNNS@SiO2@Al2O3 with strong physical blocking effect can form a physical barrier to prevent heat and oxygen from entering the internal polymer matrix, and can enhance the density and strength of the carbon layer, so as to improve the fire resistance of the material. In addition, the BNNS@SiO2@Al2O3 uniformly dispersed in the epoxy resin can more effectively form a heat-conducting network, and can reduce phonon scattering at the interface, so that the heat-conducting performance of the composite material is also significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a BNNS@SiO2@Al2O3 / cashew phenol-based flame-retardant and thermally conductive epoxy composite material and its preparation method, belonging to the field of chemical materials technology. Background Technology

[0002] As high-performance semiconductor devices and integrated packaging become increasingly miniaturized and compact, the thermal effects resulting from high power density and high integration inevitably become more severe. Therefore, effective heat dissipation is crucial for the development of integrated circuit chips. Typically, thermal interface materials connecting heat sources and heat sinks can effectively prevent overheating and its resulting equipment damage. Epoxy resin is widely used as a polymer matrix in thermal interface materials due to its excellent mechanical strength, insulation properties, and ease of processing. However, the thermal conductivity of epoxy resin is far from meeting the heat dissipation requirements of integrated circuit chips. Therefore, there is an urgent need to develop high-performance epoxy resin composite materials with high thermal conductivity.

[0003] Previous research has largely focused on improving the thermal conductivity of epoxy resin matrices by introducing single or mixed thermally conductive fillers. Boron nitride nanosheets (BNNS) have garnered significant attention among reported thermally conductive fillers due to their higher thermal conductivity (600 W / mK) resulting from reduced phonon-phonon scattering and deviating from two-dimensional (2D) selection rules in interlayer interactions and coupling. To achieve higher thermal conductivity, a large amount of filler is typically added to the epoxy resin matrix, inevitably leading to high viscosity (reduced processability), compromised dielectric properties, and increased cost, thus hindering the achievement of desired heat dissipation efficiency. According to the widely accepted theory of thermal conduction pathways, constructing an effective thermal conduction network within the epoxy resin matrix is ​​crucial for improving the thermal conductivity of low-filler-content epoxy resin composites. The smaller thickness of BNNS facilitates the formation of thermal conduction networks within the polymer, making its use effective for improving the thermal conductivity of epoxy resins. Furthermore, compared to single fillers, mixed fillers have an increased probability of contact and overlap, thus facilitating the formation of thermal conduction pathways and achieving even higher thermal conductivity. However, the adhesion between mixed fillers depends only on physical deposition and adsorption, which inevitably leads to more defects and interfacial thermal resistance, worsens phonon scattering, and causes filler agglomeration.

[0004] Therefore, although incorporating BNNS into the epoxy resin composite matrix can improve the fire resistance of the composite by forming a physical barrier to block heat and oxygen, the flame-retardant effect of adding BNNS alone is not satisfactory due to the extremely high flammability of epoxy resin itself and the compatibility issues between BNNS and the matrix material. Thus, how to modify BNNS to better improve its thermal conductivity and flame-retardant properties, and how to further improve the fire safety performance of epoxy resin composites, are problems that urgently need to be solved by those skilled in the art. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention first modifies BNNS by hydroxylation to obtain hydroxylated boron nitride nanosheets (BNNS-OH). Then, through a one-step sol-gel process using tetraethyl orthosilicate, in-situ modification and positioning of the silica precursor on the surface of BNNS-OH are achieved. Furthermore, a ternary heterostructure BNNS@SiO2@Al2O3 thermally conductive filler is prepared by bridging BNNS-OH and alumina. Finally, a fully bio-based flame-retardant epoxy resin based on a combination of bio-based flame-retardant epoxy monomers and bio-based flame-retardant epoxy curing agents is developed. Combined with the ternary heterostructure BNNS@SiO2@Al2O3 thermally conductive filler, the flame-retardant, thermally conductive, and mechanical properties of the epoxy resin composite material are significantly improved.

[0006] This invention is achieved through the following technical solution:

[0007] The first objective of this invention is to provide a method for preparing a flame-retardant and thermally conductive cashew nut shell epoxy resin composite material, comprising the following steps:

[0008] Preparation of S1, BNNS@SiO2@Al2O3 multi-component hybrid micro / nanoparticles: Hexagonal boron nitride was separated by liquid phase to obtain boron nitride nanosheets, which were then hydroxylated to obtain hydroxylated boron nitride nanosheets; the hydroxylated boron nitride nanosheets were dispersed in a solvent, the pH was adjusted to 3-5, tetraethyl orthosilicate was added dropwise and reacted at 40-60℃, and then alumina was added and reacted at 60-80℃. The product BNNS@SiO2@Al2O3 multi-component hybrid micro / nanoparticles were collected after the reaction.

[0009] S2. Preparation of phosphorus-containing cashew nut shell phenol-based flame-retardant epoxy monomer: Cashew nut shell phenol, benzyltriethylammonium chloride, and epichlorohydrin were reacted at 100–110 °C for 2–4 h; then cooled to 60–80 °C, and NaOH aqueous solution was added dropwise; subsequently, the reaction was continued at 60–80 °C for 3–8 h; after filtration, washing and purification, and drying, cashew nut shell phenol derivatives were obtained; the cashew nut shell phenol derivatives, a PH-bonded compound, and an organic solvent were mixed and reacted at 130–160 °C for 4–8 h; after the reaction was stopped and cooled, the mixture was purified, washed, and dried to obtain phosphorus-containing cashew nut shell phenol-based flame-retardant epoxy monomers;

[0010] S3. Preparation of phosphorus-containing cashew nut phenol-based flame retardant curing agent: Cashew nut phenol, a compound containing P-Cl bonds and an acid-binding agent are dissolved sequentially in an organic solvent and refluxed at 60-80 °C for 6-8 h; after washing and drying, a phosphorus-containing cashew nut phenol derivative is obtained; the phosphorus-containing cashew nut phenol derivative and maleic anhydride are reacted at 180-220 °C under an inert gas or nitrogen atmosphere for 3-5 h, and after washing and drying, a phosphorus-containing cashew nut phenol-based flame retardant curing agent is obtained.

[0011] S4. Preparation of cashew nut shell phenol-based epoxy resin composite material: The cashew nut shell phenol-based epoxy monomer synthesized in step S2 and the phosphorus-containing cashew nut shell phenol-based curing agent prepared in step S3 are mixed evenly, and then 20% to 30% of boron nitride@silicon dioxide@alumina multi-component hybrid micro / nano particles are added according to the total mass of the composite material. The mixture is mixed at 70 to 100 °C for 0.5 to 1.5 h; the mixture is cured at 110 to 130 °C for 1 to 3 h, at 140 to 160 °C for 1 to 3 h, and at 170 to 190 °C for 1 to 3 h to obtain the flame-retardant and thermally conductive cashew nut shell phenol-based epoxy resin composite material.

[0012] In one embodiment of the present invention, in step S1, the mass ratio of hydroxylated boron nitride nanosheets, tetraethyl orthosilicate and alumina is 1:(2-5):(2-3).

[0013] In one embodiment of the present invention, in step S1, the solvent is an aqueous ethanol solution.

[0014] In one embodiment of the present invention, in step S2, the molar ratio of cashew phenol, benzyltriethylammonium chloride and epichlorohydrin is 2:(1-2):(10-30).

[0015] In one embodiment of the present invention, the PH-bonded compound is one or a mixture of several of the following: DOPO, dibenzyl phosphite, diphenyl phosphite, diphenylphosphite, dimethyl phosphite, and diethyl phosphite.

[0016] In one embodiment of the present invention, in step S2, the molar ratio of cashew phenol derivative to pH-bonded compound is 1:(1-3).

[0017] In one embodiment of the present invention, in step S3, the compound containing a P-Cl bond is one or a mixture of several of the following: diphenyl chlorinated phosphate, diphenylphosphine chloride, phenyl phosphate dichloride, phenyl phosphorus dichloride, phosphorus oxychloride, phosphorus trichloride, and hexachlorocyclotriphosphazene.

[0018] In one embodiment of the present invention, in step S3, the molar ratio of cashew phenol to the compound containing P-Cl bonds and the acid-binding agent is (1-6):1:(1-6).

[0019] In one embodiment of the present invention, in step S3, the molar ratio of the phosphorus-containing cashew phenol derivative to maleic anhydride is 1:(2-12).

[0020] In one embodiment of the present invention, in step S3, the acid-binding agent is one or a mixture of several of triethylamine, tetrabutylammonium bromide, sodium hydroxide, and potassium hydroxide.

[0021] In one embodiment of the present invention, in step S2 or S3, the organic solvent is one or a mixture of several of chloroform, dichloromethane, toluene, xylene, and tetrahydrofuran, and the amount of organic solvent used is 30-80% of the total mass of the reaction system.

[0022] In one embodiment of the invention, the drying is performed using one or a mixture of anhydrous magnesium sulfate, anhydrous sodium sulfate, and sodium sulfate.

[0023] In one embodiment of the present invention, the molar ratio of cashew phenol-based epoxy monomer to phosphorus-containing cashew phenol-based curing agent is 16:(1-12).

[0024] The second objective of this invention is to provide a BNNS@SiO2@Al2O3 / cashew phenol-based flame-retardant and thermally conductive epoxy composite material prepared by the method described above.

[0025] A third objective of this invention is to provide the application of the BNNS@SiO2@Al2O3 / cashew phenol-based flame-retardant and thermally conductive epoxy composite material in circuit board manufacturing.

[0026] The beneficial effects of this invention are:

[0027] 1. The epoxy resin composite material prepared by this invention has higher thermal conductivity: Compared with the traditional method of introducing single or mixed fillers to improve the thermal conductivity of epoxy resin composite materials, this material constructs a ternary thermally conductive system BNNS@SiO2@Al2O3. Through the ternary heterostructure thermally conductive filler, the characteristics of multi-element fillers can be fully utilized, forming a more efficient thermal conduction path in the matrix, and effectively avoiding interfacial thermal resistance and incomplete dispersion of fillers, ultimately achieving a synergistic improvement effect on the thermal conductivity of the composite material.

[0028] 2. Excellent sustainability: Compared with traditional single biomass component epoxy resin composites, this material achieves full biomassification of epoxy resin through the combination of cashew nut phenol-based flame-retardant epoxy monomer and cashew nut phenol-based flame-retardant curing agent, reducing the dependence of epoxy resin on petroleum-based precursors and exhibiting higher environmental friendliness and sustainability.

[0029] 3. Excellent Flame Retardant Properties: Cashew nutshell-based flame-retardant epoxy monomers and cashew nutshell-based flame-retardant curing agents were simultaneously synthesized through chemical grafting reactions between cashew nutshell-based epoxy monomers and PH compounds, and between cashew nutshell-based curing agents and P-Cl compounds. Compared to traditional epoxy resin composites that only undergo single-component flame-retardant modification, this material exhibits superior flame-retardant properties. Furthermore, the ordered arrangement of BNNS@SiO2@Al2O3, with its strong physical barrier effect, can prevent heat and oxygen from penetrating the internal polymer matrix by forming a physical barrier, while simultaneously enhancing the density and strength of the char layer, further improving the fire resistance of the composite material. Detailed Implementation

[0030] The present invention will be further illustrated below with specific examples. These embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0031] Raw material source:

[0032] Cashew phenol was supplied by Cardläne (Zhuhai, China): a pale yellow liquid composed of 41% triene, 36% diene, 20% monoene, and 3% saturated compounds. Phenylene dichloride (98%), hexachlorocyclotriphosphazene (98%), diphenyl chlorophosphate (97%), 3-chloroperoxybenzoic acid (85%), tetraethyl orthosilicate, diphenyl phosphite, diphenylphosphite (98%), dimethyl phosphite (98%), and boron nitride (10 μm) were all purchased from Aladdin Chemical Co., Ltd. (Shanghai, China). Phosphorus oxychloride, chloroform, dichloromethane, anhydrous sodium sulfate, and triethylamine were all purchased from Sinopharm Chemical Reagent Co., Ltd. Al₂O₃ (particle size 1-2 μm) was purchased from Zhichuan Technology Co., Ltd. (Nantong, China).

[0033] Test method:

[0034] Limiting Oxygen Index (LOI): The sample (size: 100 mm × 6.5 mm × 3.2 mm) was tested on an HC-2 type oxygen index analyzer (Jiangning, China) in accordance with GB / T 2406.2-2009 standard.

[0035] Cone calorimeter test: According to ISO 5660-1 standard, the sample (100mm × 100mm × 4mm) was placed in aluminum foil, and the thermal radiation flux was 50 kW / m². 2 .

[0036] Thermal conductivity testing: Thermal diffusivity (α) and specific heat (Cp) were measured using a laser flash analyzer (LFA 467 Nanoflash, NETZSCH, Germany). The density (ρ) of the specimen was estimated by measuring its volume and mass. The TC value of the sample was obtained using the typical equation: TC = α × Cp × ρ.

[0037] The technical solution of the present invention will be described in detail below with reference to specific embodiments. In the following embodiments, unless otherwise specified, the reagents, materials and equipment used can be purchased commercially, prepared by conventional methods, or commonly used in the industry.

[0038] Example 1: Preparation of a cashew nut shell phenol-based epoxy resin composite material with flame retardant and thermally conductive properties

[0039] (1) First, 10 g of h-BN powder was mixed with 200 mL of 2 mol / L NaOH aqueous solution, ball-milled for 24 h, washed, purified, and dried. The above boron nitride was dispersed in a 1:1 mixture of water and isopropanol in 400 mL, sonicated, centrifuged, washed, and dried to obtain BNNS. Next, 5 g of BNNS was added to a mixture of 100 mL of ethanol and 200 mL of water, and sonicated for 30 min. After adjusting the pH to 4, 25 mL of tetraethyl orthosilicate was added dropwise and reacted at 60 °C for 12 h. Finally, 25 g of Al2O3 was added to the mixed solution and reacted at 80 °C for 18 h. The product was collected by centrifugation, washed, purified, and dried to obtain boron nitride@silicon dioxide@alumina multi-component hybrid micro / nanoparticles (BNNS@SiO2@Al2O3).

[0040] (2) 0.1 mol cashew nut shellac, 0.1 mol benzyltriethylammonium chloride, and 1 mol epichlorohydrin were reacted at 105 °C for 4 h; then, 40% NaOH aqueous solution was added dropwise at 70 °C. The reaction was continued at 70 °C for another 4 h, followed by filtration, washing, and purification. The product was then thoroughly dried to obtain the cashew nut shellac-based epoxy monomer. The cashew nut shellac-based epoxy monomer, 0.2 mol diphenyl phosphite, and 500 mL xylene were dissolved in a round-bottom flask and reacted at 140 °C for 6 h. After the reaction was stopped and cooled, the product was purified, washed, and finally dried to obtain the phosphorus-containing cashew nut shellac-based flame-retardant epoxy monomer.

[0041] (3) Dissolve 0.3 mol of cashew nut shellac and 0.3 mol of triethylamine sequentially in 100 mL of chloroform, mix thoroughly, and then add 0.2 mol of phenyl phosphorus dichloride dropwise to the mixture. Reflux at 70 °C for 7 h, and wash and purify to obtain a phosphorus-containing cashew nut shellac derivative. Next, react 0.1 mol of the phosphorus-containing cashew nut shellac derivative with 0.4 mol of maleic anhydride at 200 °C under nitrogen for 4 h, and wash and purify to obtain a phosphorus-containing cashew nut shellac-based flame retardant curing agent.

[0042] (4) The synthesized cashew nut phenol-based epoxy monomer and phosphorus-containing cashew nut phenol-based curing agent were mixed evenly at a molar ratio of 4:1. Then, 0%, 20%, 24%, 28%, and 30% of BNNS@SiO2@Al2O3 by mass of the total composite material were added respectively, and the mixture was mixed at 80°C for 1 h. Subsequently, the mixture was poured into a mold and cured at 120°C for 2 h, 150°C for 2 h, and 180°C for 2 h to obtain cashew nut phenol-based epoxy resin composite materials with flame retardancy, thermal conductivity, and toughening properties, which were respectively designated as composite material-1, composite material-2, composite material-3, composite material-4, and composite material-5.

[0043] The cashew nut shell phenol-based epoxy resin composite material obtained in Example 1 was subjected to performance testing, and the test results are as follows:

[0044] Table 1

[0045]

[0046] The results show:

[0047] As the amount of BNNS@SiO2@Al2O3 added increases, the limiting oxygen index of the composite material also rises. Simultaneously, the PHRR and THR of the composite material gradually decrease. The reduction in peak heat release rate and total heat release indicates an improvement in the flame retardant performance of the composite material, a conclusion consistent with the upward trend of the limiting oxygen index.

[0048] With increasing amounts of BNNS@SiO2@Al2O3, the thermal conductivity of the composite material significantly increases. However, once the BNNS@SiO2@Al2O3 content reaches 28%, further addition of BNNS@SiO2@Al2O3 leads to a decrease in thermal conductivity. This is because the addition of nanoparticles alters the phonon scattering and coupling within the material. At lower nanoparticle contents, their interaction with the matrix enhances phonon scattering, reducing the mean free path of phonons and thus increasing thermal conductivity. However, when the nanoparticle content exceeds a certain value, phonon scattering becomes more complex. Excessive nanoparticles cause phonons to encounter more scattering centers during transmission, further reducing the mean free path and consequently decreasing thermal conductivity. Therefore, it can be considered that when the BNNS@SiO2@Al2O3 content reaches 28%, the composite material exhibits good overall performance.

[0049] Example 2: Effect of different pH compounds on the preparation of cashew nut shell epoxy resin composites containing phosphorus-containing cashew nut shell epoxy monomers

[0050] The specific implementation method is the same as the preparation method of composite material-4 in Example 1, in which BNNS@SiO2@Al2O3 accounts for 28% of the total mass of the composite material. The difference is that the diphenyl phosphite in step (2) is adjusted to DOPO, diphenylphosphite, and dimethyl phosphite, while other conditions remain unchanged, to prepare a cashew phenol-based epoxy resin composite material with flame retardancy, thermal conductivity, and toughening properties.

[0051] The cashew nut shell phenol-based epoxy resin composite material obtained in Example 2 was subjected to performance testing, and the test results are as follows:

[0052] Table 2

[0053]

[0054] The results show:

[0055] After altering the pH compound in the preparation process of the phosphorus-containing cashew nut shell phenol-based flame-retardant epoxy monomer, the thermal conductivity of the composite material remained almost unchanged, but its flame-retardant properties decreased significantly. The composite material grafted with diphenyl phosphite exhibited the best flame-retardant properties, which may be because the phenoxy group of diphenyl phosphite and phosphorus can synergistically promote char layer formation, thus resulting in stronger flame retardancy in the condensed phase compared to other samples.

[0056] Example 3: Effect of the feeding sequence of the ternary hybrid system on the preparation of cashew nut shell phenol-based epoxy resin composites

[0057] The specific implementation method is the same as the preparation method of composite material-4 in Example 1, in which BNNS@SiO2@Al2O3 accounts for 28% of the total mass of the composite material. The difference is that the feeding order of the ternary hybrid system in step (1) is adjusted, while other conditions remain unchanged, to prepare cashew phenol-based epoxy resin composite material.

[0058] The preparation of different multi-component hybrid micro / nanoparticles includes the following specific methods:

[0059] Option 1: h-BN powder was mixed with NaOH aqueous solution and ball-milled. After washing, purification, and drying, it was dispersed in a mixed solution of water and isopropanol, sonicated for 1 h, and the detached BNNS was collected by centrifugation. BNNS and Al2O3 were dispersed in a mixed solution of ethanol and water, and after adjusting the pH to 4, tetraethyl orthosilicate was added dropwise. The mixture was magnetically stirred at 300 rpm at 80℃ for 18 h. After centrifugation, the product was collected, washed, purified, and dried to obtain boron nitride@alumina@silica multi-component hybrid micro / nanoparticles (BNNS@Al2O3@SiO2).

[0060] Option 2: First, h-BN powder is mixed with NaOH aqueous solution and ball-milled, then washed, purified, and dried. It is then dispersed in a mixed solution of water and isopropanol, sonicated for 1 h, and the detached BNNS is collected by centrifugation. Al2O3 is dispersed in a mixed solution of ethanol and water, the pH is adjusted to 4, and tetraethyl orthosilicate is added dropwise. The mixture is stirred at 300 rpm for 18 h at 80℃. Then, BNNS is added to the mixed solution, and the mixture is magnetically stirred at 300 rpm for 12 h at 60℃. After centrifugation, the product is collected, washed, purified, and dried to obtain boron nitride@silicon dioxide@alumina multi-component hybrid micro / nanoparticles (Al2O3@SiO2@BNNS).

[0061] The obtained cashew nut phenol-based epoxy resin composite material was subjected to performance testing, and the test results are as follows:

[0062] Table 3

[0063]

[0064] The results show:

[0065] Adjusting the timing of Al2O3 addition resulted in varying degrees of reduction in the flame retardancy and thermal conductivity of the composite material. First, blending BNNS with Al2O3 before adding tetraethyl orthosilicate (TES) may lead to competition between Al2O3 and BNNS surfaces for adsorption of silicic acid species, potentially resulting in a physical mixture of Al2O3@SiO2 and BNNS rather than an ordered trilayer structure. Because BNNS is not coated with SiO2, the interfacial thermal resistance of the composite material increases, and the longitudinal thermal conductivity weakens, ultimately leading to a decrease in thermal conductivity.

[0066] Adding Al2O3 first, followed by tetraethyl orthosilicate (TEE) and BNNS, may cause TEOS to hydrolyze and condense on the Al2O3 surface, forming an Al2O3@SiO2 core-shell structure. The subsequently added BNNS then struggles to bond with the existing SiO2 layer. Since there is no chemical bond between BNNS and Al2O3@SiO2, phase separation easily occurs, leading to decreased interfacial compatibility of the composite material. This results in numerous interfacial defects within the material, discontinuous heat conduction paths, and ultimately, reduced thermal conductivity.

[0067] The original addition order ensures that SiO2 is uniformly nucleated on the BNNS surface, forming a dense insulating layer. Al2O3 is then bonded to the SiO2 surface via hydroxyl condensation, enhancing interfacial bonding. This results in a ternary thermally conductive particle structure with BNNS as the thermally conductive core, SiO2 as the interfacial buffer layer, and Al2O3 as the outer protective / reinforcing phase. This combination reduces phonon scattering through chemical bonding, improving longitudinal thermal conductivity and thus exhibiting optimal thermal conductivity.

[0068] Example 4: Effect of pH on BNNS@SiO2@Al2O3 multi-component hybrid micro / nanoparticles

[0069] The specific implementation method is the same as the preparation steps of composite material-4 in Example 1, in which BNNS@SiO2@Al2O3 accounts for 28% of the total mass of the composite material. The difference is that the pH of the preparation process in step (1) is adjusted, and pH=4 is adjusted to pH=5, pH=6 and pH=7, while other conditions remain unchanged, to prepare cashew phenol-based epoxy resin composite material.

[0070] The obtained epoxy resin composite material was subjected to performance testing, and the test results are as follows:

[0071] Table 4

[0072]

[0073] The results show:

[0074] Changing the pH during the sol-gel process of preparing silica from tetraethyl orthosilicate (TEOS) resulted in varying degrees of decrease in the flame retardancy and thermal conductivity of the composite material. This is because TEOS hydrolyzes extremely rapidly under strongly acidic or alkaline conditions, easily leading to the agglomeration of SiO2 particles rather than uniform deposition. A pH of 4, being a weakly acidic environment, moderately slows down TEOS hydrolysis, thereby forming a dense, continuous SiO2 layer. Furthermore, at pH 4, the surface of BNNS is nearly electrically neutral or slightly positively charged, which facilitates the electrostatic adsorption of negatively charged silica species onto its surface. Therefore, as the pH increases, BNNS electrostatically repels silica species, causing free SiO2 particles to mix with BNNS instead of being coated, ultimately leading to a decrease in thermal conductivity.

[0075] Comparative Example 1: Comparison of three binary heat conduction systems

[0076] The specific implementation method is the same as the preparation steps of composite material-4 in Example 1, in which BNNS@SiO2@Al2O3 accounts for 28% of the total mass of the composite material. The difference is that three binary systems are used instead of the BNNS@SiO2@Al2O3 ternary system, while other conditions remain unchanged, to prepare cashew phenol-based epoxy resin composite material.

[0077] Option 1: h-BN powder was mixed with NaOH aqueous solution and ball-milled. After washing, purification, and drying, it was dispersed in a mixed solution of water and isopropanol and sonicated for 1 h. The detached BNNS was collected by centrifugation. BNNS and Al2O3 were dispersed in a mixed solution of ethanol and water. After adjusting the pH to 4, the mixture was magnetically stirred at 300 rpm at 80 °C for 18 h. After centrifugation, the product was collected, washed, purified, and dried to obtain boron nitride@alumina binary hybrid micro / nanoparticles (BNNS@Al2O3).

[0078] Option 2: h-BN powder was mixed with NaOH aqueous solution and ball-milled. After washing, purification, and drying, it was dispersed in a mixed solution of water and isopropanol and sonicated for 1 h. The detached BNNS was collected by centrifugation. BNNS was then dispersed in a mixed solution of ethanol and water, and after adjusting the pH to 4, tetraethyl orthosilicate was added dropwise. The mixture was magnetically stirred at 300 rpm at 80 °C for 18 h. After centrifugation, the product was collected, washed, purified, and dried to obtain boron nitride@silica binary hybrid micro / nanoparticles (BNNS@SiO2).

[0079] Option 3: Add commercially available Al2O3 to a mixed solution of ethanol and water, and sonicate for 30 min. After adjusting the pH to 4, add tetraethyl orthosilicate dropwise. Stir at 300 rpm for 12 h at 60 ℃. After centrifugation, collect the product, wash, purify, and dry to obtain alumina@silica binary hybrid micro / nanoparticles (Al2O3@SiO2).

[0080] The obtained cashew nut phenol-based epoxy resin composite material was subjected to performance testing, and the test results are as follows:

[0081] Table 5

[0082]

[0083] The results show:

[0084] Compared with composites containing the BNNS@SiO2@Al2O3 ternary system, composites containing the binary system show significantly reduced flame retardancy and thermal conductivity. This is because the ternary heterostructure thermally conductive filler can fully utilize the advantages of multi-element fillers, forming a more efficient heat conduction path, and effectively avoiding interfacial thermal resistance and incomplete filler dispersion, ultimately achieving a synergistic improvement in the thermal conductivity of the composite material.

[0085] Comparative Example 2: Comparison of three unit heat conduction systems

[0086] The specific implementation method is the same as that of composite material-4 in Example 1, in which BNNS@SiO2@Al2O3 accounts for 28% of the total mass of the composite material. The difference is that three unit systems are used instead of the BNNS@SiO2@Al2O3 ternary system, while other conditions remain unchanged, to prepare cashew phenol-based epoxy resin composite material.

[0087] The obtained cashew nut phenol-based epoxy resin composite material was subjected to performance testing, and the test results are as follows:

[0088] Table 6

[0089]

[0090] Compared with composites containing the BNNS@SiO2@Al2O3 ternary system, composites containing the unitary system show significantly reduced flame retardancy and thermal conductivity. This is because the ternary heterostructure thermally conductive filler can fully utilize the advantages of multi-element fillers, forming a more efficient heat conduction path, and effectively avoiding interfacial thermal resistance and incomplete filler dispersion, ultimately achieving a synergistic improvement in the thermal conductivity of the composite material.

[0091] Comparative Example 3: Standalone Commercial

[0092] The specific implementation method is the same as that of composite material-4 in Example 1, in which BNNS@SiO2@Al2O3 accounts for 28% of the total mass of the composite material. The difference is that DGEBA is used instead of the phosphorus-containing cashew phenolic epoxy monomer, step (2) is omitted, and other conditions remain unchanged. The epoxy resin composite material is prepared and is referred to as composite material-6.

[0093] Comparative Example 4: Commercial Hardener

[0094] The specific implementation method is the same as that of composite material-4 in Example 1, in which BNNS@SiO2@Al2O3 accounts for 28% of the total mass of the composite material. The difference is that DDM is used instead of the phosphorus-containing cashew phenol-based curing agent, step (3) is omitted, and other conditions remain unchanged. The epoxy resin composite material is prepared and is referred to as composite material-7.

[0095] Comparative Example 5: Both monomers and curing agents are commercially available.

[0096] The specific implementation method is the same as that of composite material-4 in Example 1, in which BNNS@SiO2@Al2O3 accounts for 28% of the total mass of the composite material. The difference is that DGEBA is used instead of the phosphorus-containing cashew phenol-based epoxy monomer, and DDM is used instead of the phosphorus-containing cashew phenol-based curing agent. Steps (2) and (3) are omitted. Other conditions remain unchanged. The epoxy resin composite material is prepared and is referred to as composite material-8.

[0097] The obtained epoxy resin composite material was subjected to performance testing, and the test results are as follows:

[0098] Table 7

[0099]

[0100] The results show:

[0101] In Comparative Example 3, DGEBA was used instead of the phosphorus-containing cashew nut phenol-based flame-retardant epoxy monomer. The flame-retardant effect and mechanical properties were poor, but the thermal conductivity was not much different from that of the phosphorus-containing cashew nut phenol-based flame-retardant composite material.

[0102] In Comparative Example 4, DDM was used instead of the phosphorus-containing cashew nut phenol-based flame retardant curing agent. The flame retardant effect and mechanical properties were poor, but the thermal conductivity was not much different from that of the phosphorus-containing cashew nut phenol-based flame retardant composite material.

[0103] In Comparative Example 5, DGEBA and DDM were used simultaneously to replace the phosphorus-containing cashew nut phenol-based flame-retardant epoxy monomer and the phosphorus-containing cashew nut phenol-based flame-retardant curing agent. The flame-retardant effect and mechanical properties were the worst, but the thermal conductivity was not much different from that of the phosphorus-containing cashew nut phenol-based flame-retardant composite material.

[0104] The embodiments provided above are not intended to limit the scope of the invention, nor are the described steps intended to limit the order of execution. Any obvious modifications made to the invention by those skilled in the art based on existing common knowledge also fall within the scope of protection defined by the claims.

Claims

1. A method for preparing a BNNS@SiO2@Al2O3 / cashew phenol-based flame-retardant and thermally conductive epoxy composite material, characterized in that, Includes the following steps: Preparation of S1, BNNS@SiO2@Al2O3 multi-component hybrid micro / nanoparticles: Hexagonal boron nitride was liquid-phase exfoliated to obtain boron nitride nanosheets, which were then further hydroxylated to obtain hydroxylated boron nitride nanosheets; BNNS-OH was dispersed in a solvent, the pH was adjusted to 3-5, tetraethyl orthosilicate was added dropwise and mixed evenly, and then alumina was added and reacted at 60-80℃. After the reaction, the product BNNS@SiO2@Al2O3 multi-component hybrid micro / nanoparticles were collected. S2. Preparation of phosphorus-containing cashew nut shell phenol-based flame-retardant epoxy monomer: Cashew nut shell phenol, benzyltriethylammonium chloride, and epichlorohydrin were reacted at 100-110 °C for 2-4 h; then cooled to 60-80 °C, and NaOH aqueous solution was added dropwise, and the reaction was continued for 3-8 h; after filtration, washing, purification, and drying, cashew nut shell phenol derivatives were obtained; the cashew nut shell phenol derivatives, pH-bonded compounds, and organic solvents were mixed evenly and reacted at 130-160 °C for 4-8 h; after the reaction, the mixture was purified, washed, and dried to obtain phosphorus-containing cashew nut shell phenol-based flame-retardant epoxy monomers; S3. Preparation of phosphorus-containing cashew nut phenol-based flame retardant curing agent: Cashew nut phenol, a compound containing P-Cl bonds and an acid-binding agent are dissolved sequentially in an organic solvent and refluxed at 60-80 °C for 6-8 h; after washing and drying, a phosphorus-containing cashew nut phenol derivative is obtained; the phosphorus-containing cashew nut phenol derivative and maleic anhydride are reacted at 180-220 °C under an inert gas atmosphere for 3-5 h, and after washing and drying, a phosphorus-containing cashew nut phenol-based flame retardant curing agent is obtained; S4. Preparation of cashew nut shell phenol-based epoxy resin composite material: The ternary heterostructure Al2O3@SiO2@BNNS micro-nano hybrid thermally conductive particles synthesized in step S1, the cashew nut shell phenol-based epoxy monomer synthesized in step S2, and the phosphorus-containing cashew nut shell phenol-based curing agent prepared in step S3 are mixed evenly and then cured at 90~130 °C for 1~3 h, at 140~160 °C for 1~3 h, and at 170~200 °C for 1~3 h to obtain flame-retardant and thermally conductive cashew nut shell phenol-based epoxy resin composite material. The PH-bonded compound is one or a mixture of several of the following: DOPO, dibenzyl phosphite, diphenyl phosphite, diphenylphosphite, dimethyl phosphite, and diethyl phosphite. The P-Cl bond-containing compound is one or a mixture of several of the following: diphenyl chlorinated phosphate, diphenylphosphine chloride, phenyl phosphate dichloride, phenyl phosphorus dichloride, phosphorus oxychloride, phosphorus trichloride, and hexachlorocyclotriphosphazene.

2. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of hydroxylated boron nitride nanosheets, tetraethyl orthosilicate, and alumina is 1: (2~5): (2~3).

3. The preparation method according to claim 1, characterized in that, In step S2, the molar ratio of cashew phenol, benzyltriethylammonium chloride and epichlorohydrin is 2:(1~2):(10~30).

4. The preparation method according to claim 1, characterized in that, The molar ratio of cashew phenol derivatives to pH-bonded compounds is 1:(1~3).

5. The preparation method according to claim 1, characterized in that, In step S3, the molar ratio of cashew phenol to the compound containing P-Cl bonds and the acid-binding agent is (1~6):1:(1~6).

6. The preparation method according to claim 1, characterized in that, In step S3, the molar ratio of the phosphorus-containing cashew phenol derivative to maleic anhydride is 1:(1~12).

7. The preparation method according to claim 1, characterized in that, In step S3, the acid-binding agent is one or a mixture of several of the following: triethylamine, tetrabutylammonium bromide, sodium hydroxide, and potassium hydroxide.

8. The preparation method according to claim 1, characterized in that, The molar ratio of cashew phenol-based epoxy monomer to phosphorus-containing cashew phenol-based curing agent is 16:(1~12).

9. A BNNS@SiO2@Al2O3 / cashew phenol-based flame-retardant and thermally conductive epoxy composite material prepared by the method according to any one of claims 1 to 8.

10. The application of the BNNS@SiO2@Al2O3 / cashew phenol-based flame-retardant and thermally conductive epoxy composite material according to claim 9 in the fabrication of circuit boards.

Citation Information

Patent Citations

  • Halogen-free flame-retardant epoxy resin precursor, halogen-free flame-retardant epoxy resin composition, molding compound product, preparation method and application

    CN111793091A

  • Low-smoke flame-retardant epoxy resin composite material and preparation method thereof

    CN113881192A